Could a functional artificial skeletal muscle be useful in muscle wasting?. Issue 3 (May 2016) - Fuoco, Claudia; Cannata, Stefano; Gargioli, Cesare
Abstract : Purpose of review: Regardless of the underlying cause, skeletal muscle wasting is detrimental for a person's life quality, leading to impaired strength, locomotion, and physiological activity. Here, we propose a series of studies presenting tissue engineering-based approaches to reconstruct artificial muscle in vitro and in vivo . Recent findings: Skeletal muscle tissue engineering is attracting more and more attention from scientists, clinicians, patients, and media, thanks to the promising results obtained in the last decade with animal models of muscle wasting. The use of novel and refined biomimetic scaffolds mimicking three-dimensional muscle environment, thus supporting cell survival and differentiation, in combination with well characterized myogenic stem/progenitor cells, revealed the noteworthy potential of these technologies for creating artificial skeletal muscle tissue. In vitro, the production of three-dimensional muscle structures offer the possibility to generate a drug-screening platform for patient-specific pharmacological treatment, opening new frontiers in the development of new compounds with specific therapeutic actions. In vivo, three-dimensional artificial muscle biomimetic constructs offer the possibility to replace, in part or entirely, wasted muscle by means of straight reconstruction and/or by enhancing endogenous regeneration. Summary: Reports of tissue engineering approaches for artificial muscle building appeared in large numbers in the specialized press lately, advocating the suitability of this technology for human application upon scaling up and a near future applicability for medical care of muscle wasting. Video abstract: http://links.lww.com/COCN/A9 Abstract : Supplemental Digital Content is available in the text